2023
DOI: 10.1073/pnas.2306279120
|View full text |Cite
|
Sign up to set email alerts
|

Causal evidence for a coordinated temporal interplay within the language network

Joëlle A. M. Schroën,
Thomas C. Gunter,
Ole Numssen
et al.

Abstract: Recent neurobiological models on language suggest that auditory sentence comprehension is supported by a coordinated temporal interplay within a left-dominant brain network, including the posterior inferior frontal gyrus (pIFG), posterior superior temporal gyrus and sulcus (pSTG/STS), and angular gyrus (AG). Here, we probed the timing and causal relevance of the interplay between these regions by means of concurrent transcranial magnetic stimulation and electroencephalography (TMS-EEG). Our TMS-EEG experiments… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 148 publications
0
4
0
Order By: Relevance
“…3e ). Whereas structures showing coupled fluctuations in entrainment are typically associated with processing of speech 2831 (and therefore may reflect attention to sensory input), those with corresponding α-fluctuations involve regions associated with fronto-parietal attention networks 32,33 , but also the default mode network 33,34 . Together, these results imply that fluctuations in opposing attentional modes may stem from an interaction between distinct cortical networks, one associated with active processing of external stimuli (i.e., the speech network), and the other concerned with up- and down-regulation of processing resources via inhibitory α-oscillations.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…3e ). Whereas structures showing coupled fluctuations in entrainment are typically associated with processing of speech 2831 (and therefore may reflect attention to sensory input), those with corresponding α-fluctuations involve regions associated with fronto-parietal attention networks 32,33 , but also the default mode network 33,34 . Together, these results imply that fluctuations in opposing attentional modes may stem from an interaction between distinct cortical networks, one associated with active processing of external stimuli (i.e., the speech network), and the other concerned with up- and down-regulation of processing resources via inhibitory α-oscillations.…”
Section: Resultsmentioning
confidence: 99%
“…4e ). Whereas structures showing coupled fluctuations in entrainment are typically associated with processing of speech 3336 (and therefore may reflect attention to sensory input), those with corresponding α-fluctuations involve regions associated with fronto-parietal attention networks 37,38 , but also the default mode network 38,39 .…”
Section: Resultsmentioning
confidence: 99%
“…Using similar method in a reading task, Schoffelen et al (2017) found feedforward connection from pMTG to IFG and feedback and feedforward connections between IFG and aMTG. A recent study (Schroen et al, 2023) using a subset of our stimulus material investigated temporo-frontal causal influences with a combined transcranial magnetic stimulation and electroencephalography approach. Interestingly, using this completely different approach, they also observed early feedforward influences from left pSTG to left IFG and late feedback influences (300-500ms) from left IFG to left pSTG.…”
Section: Discussionmentioning
confidence: 99%
“…Other types of studies have evaluated the interplay between nodes of the language network during specific tasks. For example, one study of concurrent transcranial magnetic stimulation and electroencephalography (TMS-EEG) revealed time-and region-specific causal evidence for a bidirectional flow of activation from the left pSTG/superior temporal sulcus (STS) to the left posterior inferior frontal gyrus (pIFG) and back during auditory sentence processing, as well as interplay between left pSTG/STS and left AG [20].…”
Section: The Left-hemisphere Language Networkmentioning
confidence: 99%